2017
DOI: 10.3847/1538-4357/836/2/218
|View full text |Cite
|
Sign up to set email alerts
|

Absence of an X-shaped Structure in the Milky Way Bulge Using Mira Variable Stars

Abstract: The stellar density distribution of the bulge is analyzed through one of its tracers. We use oxygenrich Miras variables from the Catchpole et al. (2016) survey and OGLE-III survey as standard candles. The average age of these stars is around 9 Gyr. The population traced by Mira variables matches a boxy bulge prediction, not an X-shaped one, because only one peak is observed in the density along the analyzed lines of sight, whereas the prediction of an X-shape gives two clear peaks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Because the fields are symmetrical to l = 0 • , the two RCs contribute similarly to the magnitude distribution, even though the foreground RC will contributes slightly more to the distribution at l = 1 • compared to l = −1 • ; for the background RC, the opposite is true. The X-bulge density law proposed by López-Corredoira (2017) describes well this phenomenon: by looking at Figure 13, we can clearly see how the l = 1 • line of sight will pass closer to foreground RC than to the background RC, but thanks to the viewing angle under which we observe the Bar, both RCs will be visible in the magnitude distribution, even though in different contributions. The double peaked magnitude distribution shown in yellow is the López-Corredoira (2017) model calculated using Equation 4where ρB is the X-shaped density distribution that we have shown in Figure 13.…”
Section: Data Versus Model Comparisonsupporting
confidence: 59%
“…Because the fields are symmetrical to l = 0 • , the two RCs contribute similarly to the magnitude distribution, even though the foreground RC will contributes slightly more to the distribution at l = 1 • compared to l = −1 • ; for the background RC, the opposite is true. The X-bulge density law proposed by López-Corredoira (2017) describes well this phenomenon: by looking at Figure 13, we can clearly see how the l = 1 • line of sight will pass closer to foreground RC than to the background RC, but thanks to the viewing angle under which we observe the Bar, both RCs will be visible in the magnitude distribution, even though in different contributions. The double peaked magnitude distribution shown in yellow is the López-Corredoira (2017) model calculated using Equation 4where ρB is the X-shaped density distribution that we have shown in Figure 13.…”
Section: Data Versus Model Comparisonsupporting
confidence: 59%
“…Although Mira period-luminosity (PL) relations exhibit an intrinsic dispersion in the optical (de Grijs 2011), it has been found that such dispersions are smaller at near-and mid-infrared (IR) wavelengths for Miras with thin dust shells and periods of less than 400 days (Whitelock et al 2008;Matsunaga et al 2009;Whitelock 2013). Thus, their PL relations can be used to trace the structure of the Milky Way (MW) galaxy and beyond (Catchpole et al 2016;López-Corredoira 2017). Moreover, SiO masers from Mira stars have proved powerful tools for investigating stellar motions in optically obscured regions of the MW (Fujii et al 2006;Deguchi et al 2007Deguchi et al , 2008Deguchi et al , 2010Deguchi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, using similar images of the Milky Way in the infrared, Ness & Lang (2016) have more recently claimed to see an X-shaped bulge, trying to confirm more recent theories of bulge formation (e.g., Li & Shen 2015). In spite of their claims, we do not see a clear X-shape in the raw images, and we think the processed images may also show elliptical or boxy bulges depending on the subtraction of some particular disk model (López-Corredoira 2017), or the subtraction of the bulge as an ellipsoid instead of as a boxy bulge (Han & Lee 2018).…”
Section: Introductionmentioning
confidence: 69%